Antipsychotics use increases the risk of breast cancer in Women: Findings from systematic review and meta-analysis of observational studies - Mehdi Karimi; Fatemeh Ziyafati Kafi; Samira Pirzad; Seyed Morteza Ali Pourfaraji; Sharareh Jahangiri (Comprehensive Psychoneuroendocrinology)
Background and objective: Emerging evidence suggests Antipsychotics may influence cancer risk through prolactin elevation. While studies have explored the potential link between antipsychotic use and breast cancer risk, findings remain inconsistent. A comprehensive synthesis of existing data is needed to clarify this association. This meta-analysis aimed to discover the association between antipsychotic use and the risk of breast cancer in females. Methods: A comprehensive literature search was conducted across major online databases from inception to May 2025 to identify relevant studies. Data were extracted from eligible publications, and meta-analyses were performed to estimate the pooled effect sizes. Relative risks (RRs) were used for cohort studies, while odds ratios (ORs) were used for case-control studies. Results: A pooled analysis of 13 observational studies (14 effect sizes from seven cohort and seven case-control studies) demonstrated a significant association between antipsychotic use and increased breast cancer risk (OR: 1.23; 95 % CI: 1.12–1.35; p < 0.01). Subgroup analyses showed elevated risk in both cohort studies (OR: 1.25; 95 % CI: 1.00–1.56; p = 0.046) and case-control studies (OR: 1.21; 95 % CI: 1.11–1.32; p < 0.001). First-generation antipsychotics were associated with a higher risk (OR: 1.22; 95 % CI: 1.03–1.45; p = 0.023) compared to second-generation agents (OR: 1.08; 95 % CI: 1.04–1.13; p < 0.001). Geographically, the highest risk was observed in Asian populations (OR: 1.42; 95 % CI: 1.08–1.88; p = 0.011), followed by European (OR: 1.21; 95 % CI: 1.14–1.28; p < 0.001) and North American populations (OR: 1.17; 95 % CI: 1.06–1.31; p = 0.002). Conclusions: This meta-analysis found that antipsychotic use is associated with a 23 % increased risk of breast cancer in females, with a higher risk observed for first-generation compared to second-generation antipsychotics, and particularly elevated in Asian populations. These findings emphasize the need for further research into the underlying mechanisms and regional disparities. Clinicians should carefully evaluate the risks when prescribing antipsychotics and consider regular breast health monitoring for patients undergoing long-term treatment.